_‘Tantum in Domino’_: Tertullian’s Interpretation of 1 Corinthians 7 in His Ad Uxorem - Coleman Ford (Tyndale Bulletin, 2018)
Tertullian of Carthage (c. AD 155–240) is most remembered for his adherence to the Montanist sect and subsequent moral rigidity. While various opinions exist as to the Montanist influence upon his writings, signs of such adherence are evident from an early period. This is true of his treatise _Ad uxorem_, written in the early third century. His views of marriage, specifically in light of the Pauline injunctive from 1 Corinthians 7:39, provide readers with an early, and relatively unexplored, perspective on Christian marriage. This essay examines this early treatise from Tertullian, and his interpretation of Paul, in order to better understand the complexities of Tertullian’s early view of marriage. Addressing the work of Elizabeth Clark on this topic, this essay presents the _tantum in Domino_ (‘only in the Lord’) phrase as pivotal for understanding Tertullian’s view of marriage (and subsequent remarriage) as a created good.